2015
DOI: 10.3390/antiox4020304
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin, a Flavonoid Antioxidant, Ameliorated Procarbazine-Induced Oxidative Damage to Murine Tissues

Abstract: Procarbazine (PCZ) (indicated in Hodgkin’s disease), is an alkylating agent known to generate free radicals in vivo, while Quercetin (QCT) is a flavonoid antioxidant with proven free radical scavenging capacity. This study investigated the protective effects of QCT on PCZ-induced oxidative damage in the rat. Male Wistar rats (160–180 g) were randomized into five groups (n = 5/group): I (control), II PCZ-treated (2 mg/kg body weight (bw) for seven days); III pre-treated with QCT (20 mg/kg bw) for seven days, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The findings from studies in several cellular models have indicated the ability of dietary polyphenols to counteract ROS production and its associated oxidative damage by controlling mitochondrial membrane potential and oxidative phosphorylation (33,34). Dietary polyphenols can also act indirectly by up-regulating endogenous antioxidant defenses (35,36). Furthermore, these molecules act as potent inducer of lipophagy in animal models of steatosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…The findings from studies in several cellular models have indicated the ability of dietary polyphenols to counteract ROS production and its associated oxidative damage by controlling mitochondrial membrane potential and oxidative phosphorylation (33,34). Dietary polyphenols can also act indirectly by up-regulating endogenous antioxidant defenses (35,36). Furthermore, these molecules act as potent inducer of lipophagy in animal models of steatosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…7,22,25,26 According to recent reports, avonoids possess a series of biological properties, acting on biological systems as antioxidants. [27][28][29][30] Polysaccharides have received an increased attention due to their antioxidant and hepatoprotective effects. 20,[31][32][33][34][35][36] Our results show that the WEJ was a rich source of polyphenolics, avonoids and polysaccharides which have potential antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…[32]. Serum levels of liver enzymes, ALT, AST and ALP have been shown to be reliable markers of hepatotoxicity [33].While the mean values for total protein, ALT and AST was found to be significantly increased in the experimental groups compared to control (p<0.05), the mean values for serum albumin was significantly decreased in the experimental group compared to control (p<0.05).…”
Section: Discussionmentioning
confidence: 80%